TUHA PEUT SEBAGAI LEMBAGA ALTERNATIF PENYELESAIAN SENGKETA MASYARAKAT ACEH UTARA DAN KOTA LHOKSEUMAWE - Fisa, Triansyah; Tasrizal, Tasrizal; Mahdi, Mahdi (Prodi Hukum Tata Negara Islam (Siyasah Syar'iyyah) STAIN Teungku Dirundeng Meulaboh, 2024)
The purpose of this study is to describe the beliefs of the people of North Aceh and the City of Lhokseumawe towards the dispute resolution decided by Tuha Peut as a gampong traditional institution and to describe the prospects of Tuha Peut as a customary institution in dispute resolution in the future. The research method used in this study is descriptive qualitative with a socio-legal approach. The main target in this research is the Tuha Peut institution in North Aceh and Lhokseumawe City. Data collection techniques are carried out through interviews, observation and documentation. Data processing is carried out by distributing data sets based on a predetermined problem formulation. Data analysis is in accordance with the research specifications, the existing data will be analyzed qualitatively, namely grouping the data and retelling it in the description. The results of the study indicate that the trust of the people of North Aceh and Lhokseumawe City towards dispute resolution shows that there are people who are a little distrustful, less trusting. However, more people believe in the dispute decision made by Tuha Peut because it can be scientifically justified. The prospect of Tuha Peut as a customary institution in resolving disputes in the future is very strategic because it has been regulated in Qanun No. 4 of 2003 concerning the Mukim Administration in the Province of Nanggroe Aceh Darussalam, Qanun No. 5 of 2003 concerning the Inner Village Government of Nanggroe Aceh Darussalam Province, and Qanun Number 10 of 2008 concerning the Guidance of Customary Life and Customs. However, in its development, Tuha Peut according to its functions and authorities, coupled with the ability and charisma, future prospects will shine more and have strong strength in a village.